Expediting toxicity testing with increased precision, predictive power, and clinical utility. (30th April 2018) - Pressman, Peter; Hayes, A Wallace; Clemens, Roger
Federal Government management of health risks associated with the use of therapeutics and unintended environmental chemical exposures must be expedited to meet public health needs. Although US agencies initiated the Tox21 strategy over a decade ago to expedite toxicity testing and improve the reliability of risk assessments, recent status reports indicate that achieving its goals is still decades away. Emerging technologies create an opportunity to both expedite toxicity testing and improve its predictive power. The way forward may be an augmentation of the strategy aimed at enhancing the resolution and scope of Tox21 and exploring the adaptability of real-time chemical sensor, digital imaging, and other technologies to toxicity testing. Among the anticipated returns on the associated investment would likely be enhanced accuracy in prediction, reductions in the time needed to conduct hazard identifications and toxicity assessments, and an overall increase in the precision and reliability of the risk assessment process. This in turn expedites risk management decisions and reduces scientific uncertainty and the need to incorporate margins of safety that can add cost without necessarily returning improved health protection.